2019
DOI: 10.1021/acs.jced.8b00815
|View full text |Cite
|
Sign up to set email alerts
|

Micellization and Adsorption Properties of New Cationic Gemini Surfactants Having Hydroxyisopropyl Group

Abstract: A series of cationic gemini surfactants, N,N′-bis­(alkyl)-N,N′-bis­(2-hydroxypropyl)­ethylenediammonium dibromide, [C n H2n+1(CH3CH­(OH)­CH2)­NH­(CH2)2NH­(CH2CH­(OH)­CH3)­C n H2n+1]­Br2 (where n is the tail chain length, n = 9, 12, and 14), referred to as C n C2C n [iso-Pr­(OH)] was synthesized. Via conductometric and tensiometric methods, at different temperatures (283 to 313 K), specific electrical conductivities and surface tensions of the aqueous solutions of these cationic gemini surfactants were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…Since the thermal motion in surfactant aggregates condenses with increasing temperature, β values decrease as the temperature increases (Asadov et al, 2019). The data in Table 1 confirm this idea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the thermal motion in surfactant aggregates condenses with increasing temperature, β values decrease as the temperature increases (Asadov et al, 2019). The data in Table 1 confirm this idea.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the viability of gram‐positive bacteria is remarkably decreased compared to gram‐negative organism upon treatment with IBCGS because their cell wall contains peptidoglycan (Shaban et al, 2014; Alam et al, 2019). A good adsorption capacity is one of the basic reasons for a high antibacterial impact (Asadov et al, 2019). We can say that the GS 4 and 5 have a higher adsorption capacity compared with others.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum surface excess ( Γ max ) and the area occupied by a surfactant molecule ( A min ) at the air/water interface are two important parameters for reflecting the adsorption amount and packing density of surfactant molecules at the air/water interface. Based on Gibbs adsorption isotherm theory (Asadov et al, 2019b), the values of Γ max and A min can be calculated by Eqs and . Γmax=()12.303nRTnormaldγnormaldlogCT Amin=1024NAΓmax …”
Section: Resultsmentioning
confidence: 99%
“…The possibilities of varying headgroup‐tail architecture to design novel types of surfactants have drawn increasing attention both in industrial and academic fields (Asadov et al, 2019a; Mirgorodskaya et al, 2018; Naves et al, 2013). Dendritic surfactants usually have one hydrophobic or hydrophilic chain connecting with the divergent groups like branches, where the number of branched groups arranged in a neat way can increase as the surfactant generation increases (Shavykin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that the stability of vesicles at the human body temperature also makes them candidates for use in drug release [95]. More recently, Asadov et al synthesized and characterized the cationic gemini surfactant N,N -bis(alkyl)-N,N -bis (2-hydroxypropyl) ethylene diammonium dibromide with chain lengths of 9, 12, and 14 carbon atoms [94]. They found that the aggregate diameters decreased when temperature was increased.…”
Section: Micelles Formationmentioning
confidence: 99%